Analysis of External Magnetized Dissipative Thermo-convective Tangent Hyperbolic-micropolar Flow on a Rotating Non-isothermal Cone with Hall Current and Joule Dissipation: Electro-conductive Polymer Spin Coating - S. Abdul Gaffar; O. Bég; T.A. Bég; S. Kuharat; P. Ramesh Reddy (Journal of Applied and Computational Mechanics)
Motivated by spin coating operations for magnetic polymers, a theoretical and numerical study is conducted of nonlinear, steady-state boundary layer flow and heat transfer of an incompressible tangent hyperbolic non-Newtonian micropolar fluid from a spinning cone with magnetic field, viscous dissipation, Hall current, Joule dissipation and power-law variation in temperature on the cone surface. The transformed non-dimensional conservation equations are solved numerically subject to physically appropriate boundary conditions using a second-order accurate implicit finite-difference Keller Box technique. The numerical code is validated with previous studies. Increasing magnetic interaction parameter (M) accelerates the axial velocity, damps the tangential velocity and micro-rotation (near the wall) and elevates temperatures strongly. Increasing Eckert number (Ec) enhances temperature and accelerates the axial flow and damps the tangential flow and also the angular velocity (micro-rotation) near the wall, although it generates strong angular acceleration further into the boundary layer. An increment in Hall parameter (βe) produces significant cross flow and damps the axial velocity but elevates the tangential flow and temperature (and thermal boundary layer thickness), also producing a marked acceleration in angular velocity further from the cone surface. Increasing Eringen micropolar coupling parameter K weakly reduces axial velocity near the wall but accelerates the axial flow further away. A strong acceleration in tangential flow and temperature is induced throughout the boundary layer regime with higher Eringen micropolar coupling parameter whereas. Reversal in micro-element spin (angular velocity) is suppressed near the cone surface with greater higher Eringen micropolar coupling parameter although there is a strong deceleration in the micro-rotation further towards the free stream. The simulations provide a useful insight into complex rheological magnetic spin coating operations and a solid benchmark for further computational fluid dynamics investigations.